Respuesta :
for a quadratic, is simply the quadratic itself expanded, nothing to it, so we'll just simply expand the binomial and simplify,
[tex]\bf y=2(x+4)^2-2\implies y=2(x^2+8x+16)-2 \\\\\\ y=2x^2+16x+32-2\implies y=2x^2+16x+30[/tex]
[tex]\bf y=2(x+4)^2-2\implies y=2(x^2+8x+16)-2 \\\\\\ y=2x^2+16x+32-2\implies y=2x^2+16x+30[/tex]
Answer:
The standard form of the equation of a parabola is [tex]y=2x^2+16x+11[/tex]
Step-by-step explanation:
Given : The vertex form of the equation of a parabola is [tex]y=2(x+4)^2-21[/tex].
To find : What is the standard form of the equation?
Solution :
The standard form of the equation of a parabola is the expansion of the vertex form,
Now, we open the square term of the vertex form and solve it
[tex]y=2(x+4)^2-21[/tex]
[tex]y=2(x^2+4^2+2(x)(4))-21[/tex]
[tex]y=2(x^2+16+8x)-21[/tex]
[tex]y=2x^2+32+16x-21[/tex]
[tex]y=2x^2+16x+11[/tex]
Therefore, The standard form of the equation of a parabola is [tex]y=2x^2+16x+11[/tex]